Rare Earth Doped Optical Fibers with Multi-section Core - Chongyuan Huang; Jihong Geng; Tao Luo; Jiali Han; Qing Wang; Rongguang Liang; Shanhui Fan; Shibin Jiang (iScience, 2019)
Summary: The gain bandwidth of a single-mode fiber is limited by the atomic transitions of one rare earth gain element. Here we overcome this long-standing challenge by designing a new single-mode fiber with multi-section core, where each section is doped with different gain element. We theoretically propose and experimentally demonstrate that this configuration provides a gain bandwidth well beyond the capability of conventional design, whereas the inclusion of multiple sections does not compromise single-mode operation or the quality of the transverse modal profile. This new fiber will be beneficial in realizing all fiber laser systems with few-cycle pulse duration or octave tunability. : Optics; Fiber Optics; Optical Materials Subject Areas: Optics, Fiber Optics, Optical Materials